2011
DOI: 10.1111/j.1537-2995.2010.02758.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of short‐term handling and storage conditions for marrow and peripheral blood stem cell products

Abstract: Seventy-two-hour storage of BM, PBSC, and PBMNC products at refrigerated temperature maintains optimal cell viability and recovery. Anticoagulation with ACD-A is preferred over heparin to reduce lactic acid accumulation in the product media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 20 publications
4
40
0
Order By: Relevance
“…The high level of late stage apoptosis of cells stored at 10 × 10 6 cells/ml may be explained that the highest cell concentration may be associated with the fastest lactic acid accumulation (Kilkson, Holme & Murphy, 1984). To some extent, decreasing cell concentration to limit lactic acid accumulation could enhance cell viability and improve cell function (Kao, Kim & Daley, 2011). Long-term proliferation kinetics results indicated that the proliferation potential of cells stored at 1 × 10 6 cells/ml was impaired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high level of late stage apoptosis of cells stored at 10 × 10 6 cells/ml may be explained that the highest cell concentration may be associated with the fastest lactic acid accumulation (Kilkson, Holme & Murphy, 1984). To some extent, decreasing cell concentration to limit lactic acid accumulation could enhance cell viability and improve cell function (Kao, Kim & Daley, 2011). Long-term proliferation kinetics results indicated that the proliferation potential of cells stored at 1 × 10 6 cells/ml was impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors including preservation media, durations of storage and cell concentrations may affect the viability and function of MSCs when suspended in liquid storage medium (Lane et al, 2009; Kao, Kim & Daley, 2011; Chen et al, 2013). Different kinds of preservation media including M199 (Mohamadnejad et al, 2007), PBS (Wang et al, 2011), NS (Venkataramana et al, 2010), PlasmalyteA (Chen et al, 2013), 1% HSA in DMEM (Lane et al, 2009), 20% HSA and 5% glucose in Ringer’s lactate (Gálvez-Martín et al, 2014) have been used in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…With collection centers often being distant from specialized cell processing laboratories, there is a clear need to define shipping and storage conditions to optimize downstream cell viability and function. Temperature, cell concentration, and cell content are the usual variables associated with optimization of hematopoietic progenitor cell therapy product stability . Cold temperature and lower cell concentration seem to limit the effects of cell metabolism during holding or transport.…”
Section: Discussionmentioning
confidence: 99%
“…Mobilized peripheral blood stem cell products have been extensively characterized for optimal transport and storage: refrigerated temperatures appear to maintain optimal product quality (e.g., viability), while concentrations of 200 × 10 6 nucleated cells/mL or greater appear detrimental . There has been much less reported on nonmobilized MNC products collected from peripheral blood, whether from apheresis or whole blood . However, nonmobilized peripheral blood MNC collections are a common starting material for novel cell therapies, including natural killer cells, dendritic cells, cytotoxic T cells, and regulatory T cells .…”
mentioning
confidence: 99%
“…13 Complexities associated with cellular products, such as variable and heterogeneous cellular content and the demands of specificity of patients and donors emphasize the need for computerized systems and demonstrate the challenges of managing all aspects of cell collection, preparation, ordering, and administration of these products. 14,15 Although the ordering process for cellular therapies has not been previously automated, considerable progress has been made in the development of computerized order entry systems for standard drugs for physicians, nurses, and other providers. Systems have been developed for ordering of chemotherapy that contain special functionalities, including dose calculations based on body-surface area or area-under-the-curve dosing, multiple checks for maximum and cumulative dosing, and complex dose schedules required for chemotherapy medications.…”
Section: Introductionmentioning
confidence: 99%